Machine Noise Intensity And Workers Stress Level Of Jewelry Factory In Surabaya - Cyntia, Amelia; Wendra, Sadya; Wattimena, Inge (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Working with uncomfortable conditions over time will cause stress. Stress caused by noise can be increased if not handled seriously Aim: This study is aimed to analyze the correlation between machine noise intensity and workers’ stress level of jewelry factory in Surabaya. Methods: This research use an analytic survey with the type of research design used is a cross-sectional research design. The population in this study involved 110 production employees in the jewelry factory in Surabaya in 2017. Sampling technique in this research is nonprobability sampling that is purposive sampling or judgmental sampling. Respondents who met the inclusion criteria were 87 people. The intensity measurement of noise is using the Sound Level Meter on each machine that is in the production section 3 times then counted on average. The measurement of job stress is using a validated questionnaire. Spearman correlation test has done to know the correlation between variables. Result: There is a significant and strong positive relationship (p = 0.000, R = 0.696) between machine noise intensity and workers’ stress level of jewelry factory in Surabaya. Conclusion: This study showed that the higher the intensity of engine noise, the higher the level of stress generated. Education through Health Promotion is important to do in all industry sectors using voiced machines for better worker’s welfare